THE INFLUENCE OF SOCIAL PRESTIGE, EARNING POTENTIAL, AND ACCOUNTING KNOWLEDGE ON ACCOUNTING STUDENTS' INTEREST IN PURSUING A CAREER AS A PUBLIC ACCOUNTANT - Priscilla, Agatha; Dian Efriyenti (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This research explores how social prestige, earning potential, and knowledge of accounting affect the career interest of accounting students in becoming public accountants. The study stems from the observed lack of enthusiasm among accounting graduates to pursue this career path, even though public accountants hold a key position in promoting transparency in financial reporting. Employing a quantitative research design and survey technique, data were gathered through questionnaires distributed to 95 accounting students in their third semester or beyond across several universities in Batam City. The results of multiple linear regression analysis by using SPSS software indicated that each of the three variables- social prestige, earning potential, and accounting knowledge positively and significantly influence students' interest in this profession, both independently and collectively. These results provide valuable insights for universities to craft initiatives that can inspire more students to consider careers in public accounting.